The Role of Cultural Values in Feeding Practices among Children with Stunting in Jembrana Regency: A Qualitative Approach - Agustina, Komang Srititin; Kesumawati, Ketut Anom Sri (Babali Publisher, 2025)
Introduction: Stunting remains a public health problem in Jembrana Regency, Bali. Despite a decline in prevalence, persistent cases suggest that cultural and nutritional factors influence feeding practices. This study aimed to explore cultural meanings and practices shaping feeding behaviors among children with stunting. Methods: This study employed a qualitative approach with an ethnographic design. The subjects of this study were 10 mothers or caregivers of children aged 12 - 59 months with stunting, residing in Jembrana Regency, and one healthcare worker was selected using a purposive sampling technique. Data were collected through an in-depth interview guide, an observation sheet, documentation, and field notes. The collected data were then analyzed using a thematic analysis approach. Data validity was ensured through triangulation, peer debriefing, and member checking. Results: The study identified four main themes that reflect how cultural values shape feeding behaviors in children with stunting. These themes include: (1) Snacks as substitutes that reduce appetite for main meals; (2) Normalization of small body size; (3) Flexibility expressed as